Mokslinio straipsnio atsiradimas ir vystymasis XVII–XVIII amž. - Samėnas, Alvydas (Knygotyra, 1976)
To fix the results of the research activities in the XVII–XVIII centuries there were broadly used small, amorphous and ephemerical publications. On the basis of analysis could be drawn, that the scientific paper of the modern type has received its contemperary shape in the first half of the XVIII century in the proceedings of the scientific societies and at the end of the XVIII century in the substantive scientific journals. This conclusion may be important not only in handling problems of the history of scientific communications but also in defining the model of a self-organizing system of the development of science.